Differences Quality of Life According to Weekly Running Frequency among Members of the Fakerunners Bandung Community: A Cross-Sectional Study - Muhammad Anugrah Al-Khaliq; Mohammad Zaky; Septian Williyanto (Universitas Negeri Jakarta Postgraduate of Physical Education Departments, 2026)
This study aims to determine whether members of the Fakerunners Bandung running community who exercise at high frequency (≥3 times/week) have significantly better quality of life compared to those who exercise at low frequency (1–2 times/week). This research employed an comparative cross-sectional study, in which the independent variable (exercise frequency) was not manipulated but had naturally occurred prior to data collection .The population consisted of 846 active members registered in the community WhatsApp group. Purposive sampling was employed, yielding 60 respondents who met the inclusion criteria, divided equally into two groups: low frequency (1-2x/week, n=30) and high frequency (≥3x/week, n=30). The Indonesian version of the WHOQOL-BREF tool was used to assess quality of life. Shapiro-Wilk was used to evaluate normality, and Independent Sample T-tests were performed for group comparisons (all domains exhibited normal distribution). Findings indicated that the high-frequency group consistently achieved elevated average scores in all areas. Notable differences were observed in the psychological domain (p=0.013) and environmental domain (p=0.001), whereas the physical (p=0.053) and social relationship (p=0.182) domains failed to attain statistical significance. To sum up, exercising more frequently (≥3x/week) is linked to improved overall quality of life, especially in the psychological and environmental aspects.